A rare cause of hemosuccus pancreaticus: Primary splenic artery aneurysm ruptured into pancreatic serous cystadenoma - Binnur PINARBAŞI; Şule POTUROĞLU; Hakan YANAR; Koray GÜVEN; Filiz AKYÜZ; Ferhunde DİZDAROĞLU; Mine GÜLLÜOĞLU; Korhan TAVİLOĞLU; Sabahattin KAYMAKOĞLU; Zeynel MUNGAN (Turkish Journal of Gastroenterology, 2019)
-